2001
DOI: 10.2460/ajvr.2001.62.1149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a bioactive glass on healing of closed skin wounds in dogs

Abstract: Bioactive glass in soft tissues does not cause a gross inflammatory reaction but causes an increase in histologic signs of inflammation, which decreases with time. Bioactive glass has potential for increasing tissue strength. Increased subcutaneous breaking strength could be beneficial in treating wounds in which early healing strength is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 8 publications
1
31
0
1
Order By: Relevance
“…In one previous clinical study, the authors reported a poor healing 4 months after femtosecond assisted top-hat keratoplasty, requiring new sutures [25]. By contrast, in vitro studies have shown that glass particles may increase skin wound healing and subcutaneous breaking strength in dogs, by activating fibroblasts and myofibroblasts proliferation and migration [26].…”
Section: Discussionmentioning
confidence: 96%
“…In one previous clinical study, the authors reported a poor healing 4 months after femtosecond assisted top-hat keratoplasty, requiring new sutures [25]. By contrast, in vitro studies have shown that glass particles may increase skin wound healing and subcutaneous breaking strength in dogs, by activating fibroblasts and myofibroblasts proliferation and migration [26].…”
Section: Discussionmentioning
confidence: 96%
“…Understanding the mechanisms responsible for clinical success of the borate nanofibers should lead to many new applications in soft tissue repair and regeneration. Studies have also shown that small powders of 45S5 silicate-based glass can also be effective in accelerated wound healing [25]. [26] Understanding the effect of bioactive stimuli on angiogenesis offers the potential for designing a wide range of new applications, including cardiovascular repair [27][28][29].…”
Section: Soft Connective Tissue Repair and Regenerationmentioning
confidence: 99%
“…Quickly mixed with blood, they could thus prevent large blood loss. Their positive impact onto wound healing also has been shown by applying micron sized bioactive glass particles into open wounds before sewing them: with no increase in inflammatory reaction compared to control wounds, newly formed subcutaneous tissues presented higher breaking strength [79]. Studies have also shown the impact of bioactive glass particles design.…”
Section: Materials Design For Biomedical Applicationsmentioning
confidence: 99%